Presence system using RFID and ESP32 CAM based on Internet of Things - Kelvin; Eliza, Fivia; Elvanny Myori, Dwiprima; Faradina, Nevi (Journal of Industrial Automation and Electrical Engineering, 2024)
RFID enables fast and accurate user identification via radio waves, while ESP32-CAM, an ESP32 microcontroller-based camera module, adds a layer of security through visual verification. Optimizing the attendance process by reducing the time required for attendance recording, thereby reducing disruption to daily activities. The RFID and ESP32Cam Attendance System Based on the Internet off things "is by attaching the RFID card in front of the RFID reader. The RFID reader will read the unique ID contained in the card. The ESP32-CAM connected to the RFID reader will receive data from the RFID card. The ESP32-CAM will process this information and record the employee's entry or exit time. The ESP32-CAM will use an internet connection (Wi-Fi or cellular) to send employee attendance data to Google Sheet as a storage for attendance data, such as: (employee ID, entry/exit time, and date) This allows overall attendance data management. Based on the results of the tests and discussions carried out, the tool that was made has been successfully tested and works well. From the tests that have been carried out, in order for the card to be read properly, the maximum distance of the card from the sensor is 3cm. The process of sending data to Spreadsheet takes an average of 4 seconds. The speed of sending also depends on the speed of internet access. Esp32 CAM works well in sending photos to Google Drive The author hopes that this tool can be developed further by using the website and adding fingerprint sensors and Face detection